The Association Between Adverse Childhood Experiences and Different Types of Offending Behavior: An Examination Across Two Generations of British Males - Craig, Jessica M. (International journal of offender therapy and comparative criminology, 2025)
Research has established a relationship between trauma exposure, often conceptualized as Adverse Childhood Experiences (ACEs), and offending, with some evidence suggesting that both trauma and offending can be transmitted from one generation to the next. Further, while some evidence suggests that experiencing a high number of ACEs is associated with different types of offenses, it is not known whether these associations are similar across generations. The current study aims to address this gap in knowledge by examining the effects of ACEs on different offense types across two generations, utilizing data from a longitudinal study of British male participants and their male children. Results suggest that high ACE scores are associated with several offense types within generations, but the effect of parental ACEs on the subsequent generation’s offending was weak. Alongside a discussion of these findings, study limitations and future research directions are also presented.